UTILIZATION OF WATER HYACINTH FROM EUTROPHICATED WATER OF EMBUNG GRABAG PURWOREJO FOR PRODUCTION OF POWDERED HUMIC ACID - Piranti, Agatha Sih; Aprianti, Kirani; Proklamasiningsih, Elly; Mumpuni, Aris; Rahayu, Diana Retna Utarini Suci; Nurdin, Nurdin; Nasihin, Iing (Proceeding ICMA-SURE; Part 2. Proceeding The 8th International Conference on Multidisciplinary Approaches for Sustainable Rural DevelopmentDO - 10.20884/2.procicma.2025.4.1.21457, 2026)
One solution to overcome the problem of water eutrophication is to utilize water hyacinth for humic acid production. In this process, additional materials are needed as a carbon source and a microorganism activator. The objectives of this study were (1) to determine the interaction between plant parts and molasses to produce the highest humic acid. This study used a Completely Randomized Design (CRD) with two factors: plant parts (roots, stems, leaves) and concentration of molasses (50, 100, 150, 200 mLkg -1 ) for 3 times replication. The parameter measured was the production of dry weight of humic acid powder. Data analysis used ANOVA and continued with the DMRT test. The results showed that there was a significant effect of molasses concentration on the fermentation of the different plant parts. This study can be concluded that different concentrations of molasses and plant parts showed differences in the resulting humic acid production. The conclusion showed that the addition of 150 ml.kg -1 molasses to the fermentation of water hyacinth roots (AM3 treatment) produced the highest humic acid content up to  98.5 g.kg -1  or 9.5%.